2009
DOI: 10.1038/ejcn.2009.29
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effects of phytosterols

Abstract: Phytosterol and stanol (or phytosterols) consumption reduces intestinal cholesterol absorption, leading to decreased blood LDL-cholesterol levels and lowered cardiovascular disease risk. However, other biological roles for plant sterols and stanols have also been proposed. The objective of this review is to critically examine results from recent research regarding the potential effects and mechanisms of action of phytosterols on forms of cancer. Considerable emerging evidence supports the inhibitory actions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
211
0
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(223 citation statements)
references
References 72 publications
4
211
0
8
Order By: Relevance
“…On the other hand, the steroids ergosterol and ergosterol peroxide are commonly found in fungi, occurrence of phytosterols in fungi is relatively unusual (Fontaine et al 2004). The phytosterols, mainly sitosterol, have the capacity of reducing the blood cholesterol (Awad and Fink 2000), as well as phytosterols can be used to fight of cardiovascular diseases, cancer and inflammatory process (Fernandes and Cabral 2007;Woyengo et al 2009;Poli and Marangoni 2010).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the steroids ergosterol and ergosterol peroxide are commonly found in fungi, occurrence of phytosterols in fungi is relatively unusual (Fontaine et al 2004). The phytosterols, mainly sitosterol, have the capacity of reducing the blood cholesterol (Awad and Fink 2000), as well as phytosterols can be used to fight of cardiovascular diseases, cancer and inflammatory process (Fernandes and Cabral 2007;Woyengo et al 2009;Poli and Marangoni 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Встановлено, що фітостероли можуть успішно застосовуватись у боротьбі з онкологічними захво-рюваннями, зокрема, у випадках раку прямої кишки, простати та молочних залоз [5]. Стероїдні сполуки також виявляють протизапальну дію [6].…”
Section: постановка проблеми у загальному ви-гляді актуальність темиunclassified
“…On colon and prostate cancer: There is no strong and consistent evidence that sitosterol intake affects either colon or prostate cancer. (Kennedy, 1995, Klippel et al, 1997 but Woyengo et al (2009) reported the inhibitory action of phytosterols on lung, stomach and ovarian cancer. On membrane properties: Plant sterols and stanols are incorporated into cellular membranes (Child and Kuksis, 1982) and may consequently influence membrane properties.…”
Section: Effect Of Phytosterols On Different Parametersmentioning
confidence: 99%